Pendampingan Kegiatan Aksi Beberasih Pada Musala Oleh Siswa Hijaz SMAN 2 Palangka Raya - Priolawati, Melly; Surawan, Surawan; Susmiati, Susmiati (Pakis Journal Institute, 2024)
Cleanliness is an important aspect of religious life, especially in Islam, where cleanliness is considered part of the faith. The community service activity